THE STATE OF FORMATION OF READINESS OF FUTURE MATHEMATICS TEACHERS FOR DIFFERENTIATED LEARNING - Sinitska N. V. (International Journal of Innovative Technologies in Social Science, 2021)
Reforming higher pedagogical education in Ukraine involves finding ways and means of rational combination of theoretical psychological and pedagogical knowledge with the ability to apply them in practice, as well as optimizing forms and methods of teaching, improving curricula, programs and developing innovative pedagogical technologies. Today is marked by the implementation of the program of structural reform of higher education in close cooperation with other educational units, which ensures the preservation of past and national traditions, bringing the higher education system, and pedagogical in particular, in line with world scientific achievements and available budget opportunities. The formation of selected structural components of theoretical and practical readiness of teachers for differentiated learning of students in mathematics should be carried out in all types of educational activities and specially organized extracurricular activities of students to work with students, taking into account didactic and resource opportunities of information educational environment. The main means of forming readiness for differentiated learning in educational and cognitive activities in this area are specially designed tasks for the formation of selected structural components of readiness.